2009
DOI: 10.1577/t08-096.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecotype Distinctions among Steelhead in Hood River, Oregon, Allow Real‐Time Genetic Assignment of Conservation Broodstocks

Abstract: Efforts to rehabilitate threatened summer-run (SR) and winter-run (WR) populations of steelhead Oncorhynchus mykiss in the Hood River, Oregon, include operation of two conservation hatchery programs. Annual collection of discrete broodstocks relies on identification of SR and WR fish based on return time, reproductive state, and other physical and behavioral characteristics. An increased likelihood of misidentification occurs in the spring, when SR and WR return times overlap. The resulting interbreeding betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…; Matala et al. ). Distinctions likely arose due in part to selection in variable environments, characterized by in‐stream flow rate, thermal stability, and other stressors (Lytle and Poff ).…”
Section: Discussionmentioning
confidence: 97%
“…; Matala et al. ). Distinctions likely arose due in part to selection in variable environments, characterized by in‐stream flow rate, thermal stability, and other stressors (Lytle and Poff ).…”
Section: Discussionmentioning
confidence: 97%
“…In other areas, several recent genetic studies have assessed interbreeding of naturally spawning native and introduced stocks of Pacific salmon and have had similar results. For example, Matala et al (2009) found evidence of restricted gene flow between summer-run and winter-run steelhead in the Hood River, also a tributary of the Columbia River, even though there has likely been accidental mixing between the run types during artificial spawning in a hatchery. Likewise, the introduction of a nonnative lineage of Chinook Salmon O. tshawytscha in another tributary of the Columbia River has not resulted in significant introgression into the native lineage, despite overlap in their return times and spawning locations (Smith and Engle 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such is the case for all three run types, whose spawning times overlap in March-May (Figure 2) and whose spawning locations also overlap (HSRG 2009;Keefer and Caudill 2010). There are several river systems where summer-run and winter-run steelhead occur together naturally and are genetically distinct from each other (Leider et al 1984;Nielsen and Fountain 1999;Matala et al 2009). The late-winter run timing expressed by native Willamette River steelhead is believed to have evolved as an adaptation that allowed fish to access spawning areas upstream from Willamette Falls, which was impassable by steelhead for most of the year until fish passage structures were built (Myers et al 2006).…”
Section: Population Structure and Artificial Propagationmentioning
confidence: 99%
“…In reality, such programs are often contentious (see Gross 1988versus Waples 1994, much of the controversy being centered on the genetic risks associated with supplementation (Hindar et al 1991;Ryman and Laikre 1991;Waples 1994). However, hatchery supplementation is capable of helping combat the risk of extinction in natural populations (Hedrick et al 1994;Cummings et al 1997;Hedrick et al 2000;Olsen et al 2000;Matala et al 2009) or providing short-term demographic boosts (Araki et al 2007a;Berejikian et al 2008) that may benefit fisheries with low impact on existing populations (Heggenes et al 2006;Eldridge and Killebrew 2008;Matala et al 2008;Small et al 2009).…”
Section: Discussionmentioning
confidence: 99%